Bispectral index assessment in calves subjected to the continuous infusion of propofol combined with fentanyl administration - Deschk, Mauricio [UNESP]; Trein, Thomas Alexander [UNESP]; Wagatsuma, Juliana Tessalia [UNESP]; Silva, Guilherme Lopes da [UNESP]; Araujo, Marcelo Augusto de; Martins Games, Bruna de Moraes [UNESP]; Alcindo, Jefferson Filgueira [UNESP]; Rodrigues, Celso Antonio [UNESP]; Patto dos Santos, Paulo Sergio [UNESP] (Univ Federal Santa Maria, 2017)
The aim of this study was to evaluate the bispectral index (BIS) effects in calves through continuous infusion of propofol with or without fentanyl. Eight Holstein male calves (ages from six to twelve months old) with an average weight of 123 +/- 18kg were used. All animals participated in both groups, always keeping a minimum interval of one week between the anesthetic procedures; the calves were randomly distributed between groups. Anesthesia was induced with an intravenous (IV) dose of propofol of 5mg kg(-1) in control group (GP) or with propofol (4mg kg-1) associated with IV fentanyl 0.001mg kg(-1)(G(F)). All the calves were positioned in right lateral recumbency and were allowed to spontaneously breathe room air. Subsequently, the anesthesia was maintained by continuous infusion of propofol at the rate of 0.6mg kg(-1) min(-1) IV in G(P), and associated with the infusion of fentanyl 0.001mg kg(-1) hour(-1) in GF. Measurements of BIS, signal quality index (SQI) and electromyography (EMG) were evaluated before anesthesia induction (TB), and at 15, 30, 45 and 60 minutes after the beginning of continuous drugs infusion (T-15, T-30, T-45 and T-60, respectively). The heart rate (HR), respiratory rate (f), end-tidal carbon dioxide tension (ETCO2) and recovery times were evaluated as well. No significant differences were observed between the groups in the BIS variables and the recovery time was longer in GF. Co-administration of propofol and fentanyl infusions, at the doses reported here, did not change the values of BIS in cattle, but delayed the recovery time.
Keywords: calves; ruminants; balanced anesthesia; anesthetic monitoring